Ion‐Enhanced Field Emission Triboelectric Nanogenerator. Issue 37 (20th August 2019) - Chung, Jihoon; Heo, Deokjae; Shin, Gunsub; Choi, Dukhyun; Choi, Kyungwho; Kim, Dongseob; Lee, Sangmin
Abstract: As interest in triboelectric nanogenerators (TENGs) continues to increase, some studies have reported that certain limitations exist in TENG due to high potential difference, resulting in air breakdown and field emission. In addition, with known limitations such as extremely low voltage at low external resistance, a breakthrough is required to overcome the limitations of TENG. Here, a new TENG mechanism is reported, utilizing ion‐enhanced field emission (IEFE). Using a simple IEFE‐inducing layer, which consists of a charge accumulation layer and a metal‐to‐metal contact point, electrons can flow directly to a counter electrode while generating high‐output power. Under vertical contact–separation input, the generated root mean square (RMS) power of IEFE‐TENG is 635% higher compared to conventional TENG. As the fundamental mechanism of the IEFE‐TENG is based on installing this simple IEFE‐inducing layer, the power output of existing TENGs including sliding mode types can be boosted. This new TENG mechanism can be a new standard for metal–metal contact TENGs to effectively amplify the output power and to overcome potential limitations. Abstract : The ion‐enhanced field emission triboelectric nanogenerator (IEFE‐TENG) emission mechanism can be achieved by adding a simple layer. The IEFE‐TENG has a charge‐accumulating layer and a metal‐to‐metal contact point that allows electrons to flow directly to the counter electrode thereby minimizing the output loss. This new TENG mechanism can significantly increase root mean square (RMS) power of TENGs by up to 635%.